Membangun Keamanan TI yang Tangguh dengan COBIT 4.1 dan Balanced Scorecard - Darno Darno (J-CEKI : Jurnal Cendekia Ilmiah, 2024)
Implementation of technology information on an institution must be accompanied with security technology good information to address all threat about the safety information technology company related sustainability. The security that it is constituted in the law ITE number 19 year 2016 related to information technology security that is article 40 verse 1. The article account for all agencies that uses technology should be safe , this is also the case of PT. Kusuma Kreasi Utama. In ensuring safety to do evaluation or audit security ti to know value compliance with the application of keamaman IT, In doing evaluation or audit adherence to keamanaan IT can use framework cobit 4.1. Cobit 4.1 that talk about information technology security namely the domain DS5(ensure system security. In this research a level of maturity of 2.67 in hopes of compliance at least 3.00. As for the shortages because of several perpektif that is less that is , in the perspective of the decree of objectives as well as the measurement of , skills and expertise , and devices help and automation.